2019
DOI: 10.1002/jcb.28995
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spermatogenesis associated with changes in spatial arrangement of Sertoli and spermatogonial cells following induced diabetes

Abstract: The current study was conducted to assess the relationship between testicular cells in spermatogenesis, through which the production of healthy and mature sperm is essential. However, it seems necessary to obtain more information about the three‐dimensional pattern of the testis cells arrangement, which is directly related to the function of the testis after induction of diabetes. Twelve adult mice (28‐30 g) were assigned into two experimental groups: (1) control and (2) diabetic (40 mg/kg STZ). The epididymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
(109 reference statements)
3
14
0
Order By: Relevance
“…In line with other reports regarding the effect of hyperthermia on spermatogenesis (Chen et al., 2008; Edelman, 1986, 1988; Fraser et al., 1987; Fujisawa, 2006; Li et al., 2013; Sajadi et al., 2019; Vera et al., 2004), our findings confirm that transient scrotal hyperthermia can markedly decrease sperm count, sperm motility and sperm viability and impair sperm morphology. In this study, serum testosterone level shrank significantly in mice induced by scrotal hyperthermia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with other reports regarding the effect of hyperthermia on spermatogenesis (Chen et al., 2008; Edelman, 1986, 1988; Fraser et al., 1987; Fujisawa, 2006; Li et al., 2013; Sajadi et al., 2019; Vera et al., 2004), our findings confirm that transient scrotal hyperthermia can markedly decrease sperm count, sperm motility and sperm viability and impair sperm morphology. In this study, serum testosterone level shrank significantly in mice induced by scrotal hyperthermia.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have assessed the effect of hyperthermia on physiological and cellular responses of testicular tissue and its corresponding mechanism based on animal models (Edelman, 1986, 1988; Fraser, Green, Bode, & Gilula, 1987; Sajadi et al., 2019). However, there is a paucity of studies on cellular interaction and spatial arrangement of testicular cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By calculating the extent of spatial mixing and pairwise cell-cell contact frequencies between different cell types, we observed a significant disruption in spatial cellular organization of the diabetic seminiferous tubules. Of interest, a previous study using second order stereology has indicated that the spatial arrangement of Sertoli cells and spermatogonia is significantly disrupted in the diabetic testes (Sajadi et al, 2019). Indeed, our analysis showed a significant change in the spatial contact frequencies between Sertoli cells and spermatogonia.…”
Section: The Spatial Transcriptome Atlas As a Platform To Profile Spasupporting
confidence: 46%
“…Instead, we employed immunohistochemistry for distinct proteins of the BTB. Amongst others, ZO-1, claudin 11, and CX43 are structural components of the inter Sertoli cell junctions, which undergo alterations in conjunction with impairment of spermatogenesis [32,[34][35][36][37]. As shown by Rode et al [38], loss of CX43 in mouse Sertoli cells leads to spermatogenic arrest at the level of spermatogonia with only single primary spermatocytes.…”
Section: Discussionmentioning
confidence: 99%